Foamed ceramic for carbon sequestration and preparation method thereof
By introducing multi-layer structure and high-strength fibers into foam ceramic materials, combining carbon adsorption layer and hard coating, the problem of insufficient absorption and stability of existing foam ceramic materials in carbon storage is solved, and more efficient carbon is achieved Capture and underground storage performance.
Patent Information
- Application Number
- CN202411409304.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
AI Technical Summary
In the existing carbon storage technology, it is difficult to achieve the ideal carbon absorption and storage effect when foam ceramic materials are buried underground for a long time, and the pressure resistance is not enough to meet the stable demand.
Foam ceramic material with a multi-layer structure includes foam ceramic substrate, carbon adsorption layer and hard coating. Yttrium/zirconium/cerium is incorporated into the substrate, and the phase transition process from α to β phase is formed by high temperature sintering to increase hardness. High-strength fibers are also penetrated on the surface to improve the adsorption and capture effect.
It significantly improves the adsorption and capture effect of carbon dioxide, and maintains good robustness and stability when buried underground, improving the overall performance of carbon storage.
Smart Images

Figure BDA0005077556530000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam ceramics, and in particular to a foam ceramic for carbon sequestration and a preparation method thereof. Background Art
[0002] Carbon sequestration refers to the technical measures of capturing carbon and storing it safely underground to reduce the direct emission of carbon dioxide into the atmosphere, thereby mitigating climate change. Foam ceramic material is a composite material that is widely used in carbon sequestration. It is mainly used to adsorb and capture gases, act as a catalyst carrier, and replace traditional building materials. Among them, the most widely used method is to use the good stability and low permeability of ceramic foam materials, with the help of its porous structure and high specific surface area, to adsorb and capture carbon dioxide gas, and seal it in a specific regional environment to avoid carbon dioxide emissions into the atmosphere and cause climate damage.
[0003] For example, the patent with publication number CN114656278A proposes a forsterite-based foam ceramic for carbon sequestration and a preparation method thereof. The main ingredients include forsterite, natural minerals and tempering agents, and cellulose and surfactants are added. By combining additive materials and modifier materials, and through soaking and heat treatment steps, a layer of crystalline phase with higher strength is attached to the surface of the hollow pore ribs of the polyester foam ceramic, thereby increasing the physical strength of the foam plastic.
[0004] However, according to the above-mentioned records of forsterite-based foam ceramics, their compressive strength is about 6.94-7.23 MPa. This compressive strength performance level is difficult to achieve sufficient firmness and stability when used for underground storage of carbon dioxide. Summary of the invention
[0005] The technical problems to be solved by the present invention are:
[0006] Current carbon sequestration technologies face the problem of unsatisfactory or unstable carbon absorption and capture effects. Common foam ceramic materials also face great pressure and a complex underground environment when buried underground for a long time, which makes it difficult to achieve ideal results in the capture and storage of carbon dioxide, thus significantly hindering the development of carbon sequestration technology.
[0007] The technical solution adopted by the present invention is:
[0008] The present invention provides a foam ceramic for carbon sequestration, comprising a foam ceramic substrate, a carbon adsorption layer is arranged on the surface of the foam ceramic substrate, reinforcing fibers are inserted through the foam ceramic substrate and the carbon adsorption layer, and a hard coating is also arranged on the surface of the carbon adsorption layer.
[0009] Preferably, the thickness ratio of the foam ceramic substrate to the carbon adsorption layer is 1.2-2.8:1.
[0010] Preferably, the total thickness of the foam ceramic is ≤65 mm, and the thickness of the hard coating is 5-16 mm.
[0011] The present invention also provides a method for preparing the foam ceramic for carbon sequestration, comprising the following steps:
[0012] The surface of the foam ceramic substrate is coated with fiber rubber, and then coated with carbon adsorption slurry, cooled to form a carbon adsorption layer, and pressed to obtain a foam ceramic main board; the surface of the foam ceramic main board is coated with hardening paint multiple times and irradiated under ultraviolet light to form a hard coating; then transferred to a sintering furnace, evenly heated, and sintered at a heat preservation temperature to obtain foam ceramics.
[0013] Preferably, the method for preparing the foam ceramic substrate comprises the following steps:
[0014] The silicon source and the aluminum source are mixed, dissolved in deionized water, ball-milled, and then a molding aid and a surfactant are added, and a substrate blank is formed through a curing reaction;
[0015] The substrate blank is placed in a gradient temperature environment of 500±50°C, 750±50°C, 850±50°C, 1000±50°C, and 1350±50°C for segmented sintering to obtain the foam ceramic substrate.
[0016] Preferably, the foam ceramic substrate comprises, by mass fraction, 12-20% silicon source, 8-15% aluminum source, 2-5.5% molding aid, 0.3-3.5% surfactant, and the remainder is deionized water.
[0017] Preferably, the fiber sizing material comprises polyester fiber, nylon fiber and water-based polyurethane pressure-sensitive adhesive, and the fiber sizing material is coated on the foam ceramic substrate at a residual temperature of 80-110° C. while it is hot.
[0018] Preferably, the carbon adsorption slurry comprises porous particles, epoxy resin, polycarboxylate and water, and the viscosity of the carbon adsorption slurry is 350-620 mPa·s;
[0019] Wherein, the porous particles include one or more of mesoporous silica, molecular sieves, and carbon nanomaterials.
[0020] Preferably, the preparation method of the hardened coating comprises the following steps: taking 10-30 parts of epoxy acrylic resin, 3-10 parts of polysiloxane, 0.2-0.35 parts of photoinitiator, 0.2-0.3 parts of light stabilizer and 30-50 parts of organic solvent by mass, stirring at 450-600 r / min for 30-45 minutes to obtain the hardened coating.
[0021] Preferably, the hardening coating is applied in 2-4 times, and the thickness of each application is ≤6 mm.
[0022] The beneficial effects of the present invention are as follows:
[0023] The foam ceramic material in the present invention involves a multilayer structure, and high-strength fibers are inserted therein, and combined with a carbon adsorption layer and a hard coating arranged on the surface of the substrate, the adsorption and capture effect of the foam ceramic on carbon dioxide can be significantly improved. When the foam ceramic is processed into a container device for storing carbon dioxide and buried underground, it can maintain good firmness and stability.
[0024] Specifically, yttrium / zirconium / cerium are added to the foam ceramic substrate, which can improve the crystal structure of the material, and through high-temperature sintering treatment, the substrate material forms a large number of phase transition processes from α phase to β phase, so that the foam ceramic substrate has a strong hardness. The carbon adsorption layer is coated on the surface of the foam ceramic board to improve the use effect of the foam ceramic material in carbon sequestration and carbon capture, and high-strength nylon fibers and polyester fibers with outstanding durability are inserted therein, so that the foam ceramic product can maintain long-term stability when buried underground. In addition, a hard coating is added to the surface of the ceramic foam material, which can not only enhance the strength and stability of the carbon adsorption layer, but also provide a stronger carbon binding capacity and adsorption space for the adsorption of carbon dioxide through the spatial understanding structure, thereby achieving a better carbon adsorption and capture effect as well as stability in field use as a whole. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0026] The invention provides a foam ceramic for carbon sequestration, comprising a foam ceramic substrate, a carbon adsorption layer is arranged on the surface of the foam ceramic substrate, reinforcing fibers are inserted through the foam ceramic substrate and the carbon adsorption layer, and a hard coating is also arranged on the surface of the carbon adsorption layer.
[0027] The thickness ratio of the foam ceramic substrate to the carbon adsorption layer is 1.2-2.8:1, the total thickness of the foam ceramic does not exceed 65 mm, and the thickness of the hard coating is 5-16 mm.
[0028] In the present invention, the preparation method of foam ceramics for carbon sequestration comprises the following steps:
[0029] (1) Preparation of foam ceramic substrate:
[0030] The silicon source and the aluminum source are mixed, dissolved in deionized water, ball-milled, and then a molding aid and a surfactant are added to form a substrate blank through a curing reaction; the substrate blank is placed in a temperature environment of 500±50°C, 750±50°C, 850±50°C, 1000±50°C, and 1350±50°C, respectively, and sintered for 20-30 minutes each to obtain a foam ceramic substrate.
[0031] Among them, silicon source can be selected from silicon nitride, silicon carbide, etc., aluminum source can be selected from aluminum salts such as alumina or cryolite, molding aids can be selected from yttrium oxide, zirconium oxide, cerium oxide, etc., surfactants can be selected from sodium dodecyl sulfate, polyoxyethylene castor oil, etc.;
[0032] The mass proportions of the above-mentioned raw materials are respectively 12-20% of silicon source, 8-15% of aluminum source, 2-5.5% of molding aid, 0.3-3.5% of surfactant, and the balance is deionized water.
[0033] (2) Strengthening treatment:
[0034] The polyester fiber and the nylon fiber are mixed and sieved, added into the water-based polyurethane pressure-sensitive adhesive, fully stirred, and coated onto the surface of the foam ceramic substrate with a residual temperature of 80-110°C.
[0035] (3) Coating with carbon adsorption material:
[0036] The porous particles are mixed with epoxy resin, polycarboxylate and water, and stirred evenly to form a carbon adsorption slurry. After the strengthening treatment is completed, the carbon adsorption slurry is immediately and evenly coated on the surface of the foam ceramic substrate and cooled to room temperature to form a carbon adsorption layer.
[0037] Among them, the porous particles can be selected from mesoporous silica, molecular sieves, carbon nanomaterials, etc., and the viscosity of the carbon adsorption slurry is 350-620mPa·s.
[0038] (4) Suppression:
[0039] The foam ceramic plate with the carbon adsorption layer formed thereon is placed in a mold, cured and air-dried, and subjected to isostatic pressing for 3-10 minutes at a pressure of 80-110 MPa to obtain a foam ceramic main plate.
[0040] (5) Surface hardening treatment:
[0041] 10-30 parts of epoxy acrylic resin, 3-10 parts of polysiloxane, 0.2-0.35 parts of photoinitiator, 0.2-0.3 parts of light stabilizer and 30-50 parts of organic solvent are taken by mass, and stirred at 450-600r / min for 30-45min to obtain a hardened coating; the hardened coating is applied to the surface of the foam ceramic main board in 2-4 times, with the thickness of each coating not exceeding 6mm, and is placed under an ultraviolet lamp for 20-40min to obtain a foam ceramic blank.
[0042] (6) Firing and molding:
[0043] The foam ceramic blank is placed in a furnace, heated to 1120-1250°C at a rate of 3-7°C / min, and sintered for 1-2 hours to obtain the foam ceramic.
[0044] Example 1
[0045] The polyester fiber and the nylon fiber are mixed in equal amounts, passed through an 80-mesh sieve, added to 2.5 times the volume of the water-based polyurethane pressure-sensitive adhesive, stirred at 200 r / min for 20 min to obtain a reinforced slurry for later use;
[0046] Take 5.01 g of mesoporous silica, 4.63 g of molecular sieve and 5.61 g of polycarboxylate, mix them thoroughly, add them to α-epoxy resin and deionized water, and adjust the material viscosity to 450±2.5 mPa·s by adding α-epoxy resin or deionized water to obtain a carbon adsorption slurry for standby use;
[0047] 25 parts by mass of epoxy acrylic resin, 5.5 parts by mass of polysilsileoxane, 0.31 parts by mass of benzophenone-tertiary amine photoinitiator, 0.25 parts by mass of o-hydroxybenzophenone and 45 parts by mass of acetone were mixed and stirred at 550 r / min for 30 min to obtain a hardened coating for use.
[0048] Take 4.216g of silicon nitride, 4.35g of silicon carbide and 10.03g of aluminum oxide, add them to 80mL of deionized water, ball mill for 15 minutes, then add 1.6g of yttrium oxide, 1.3g of zirconium oxide and 2.66g of sodium dodecyl sulfate, stir well, and after a certain period of curing reaction, a molded substrate blank is formed; then, the substrate blank is placed at 510°C, 750°C, 830°C, 980°C, and 1350°C in turn for multi-stage sintering, sintering at each temperature for 25 minutes to obtain a foam ceramic substrate with a thickness of about 32mm.
[0049] While the foam ceramic substrate retains a residual temperature of about 95°C, about 5g of reinforcing slurry is evenly coated on the surface of the foam ceramic substrate, and then the carbon adsorption slurry is immediately coated on the surface of the reinforcing slurry. After cooling to room temperature, the foam ceramic board is placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105MPa for 3 minutes to obtain a foam ceramic main board with a carbon adsorption layer of about 15mm on the surface.
[0050] Take the foam ceramic main board, apply the hardening coating to the foam ceramic main board 4 times, each coating thickness is about 2.5 mm, place it under ultraviolet light for 30 minutes, and obtain the foam ceramic green plate.
[0051] The foam ceramic green sheet was transferred into a sintering furnace, heated to 1150°C at a rate of about 4.5°C / min, and sintered for 2 hours to obtain a foam ceramic material.
[0052] Example 2
[0053] The polyester fiber and the nylon fiber are mixed in equal amounts, passed through an 80-mesh sieve, added to 2.5 times the volume of the water-based polyurethane pressure-sensitive adhesive, stirred at 200 r / min for 20 min to obtain a reinforced slurry for later use;
[0054] Take 5.01 g of mesoporous silica, 4.63 g of molecular sieve and 5.61 g of polycarboxylate, mix them thoroughly, add them to α-epoxy resin and deionized water, and adjust the material viscosity to 450±2.5 mPa·s by adding α-epoxy resin or deionized water to obtain a carbon adsorption slurry for standby use;
[0055] 25 parts by mass of epoxy acrylic resin, 5.5 parts by mass of polysilsileoxane, 0.31 parts by mass of benzophenone-tertiary amine photoinitiator, 0.25 parts by mass of o-hydroxybenzophenone and 45 parts by mass of acetone were mixed and stirred at 550 r / min for 30 min to obtain a hardened coating for use.
[0056] Take 4.33g of silicon nitride, 4.20g of silicon carbide and 10.1g of aluminum oxide, add them to 80mL of deionized water, ball mill for 15 minutes, then add 1.65g of yttrium oxide, 1.28g of zirconium oxide and 2.8g of sodium dodecyl sulfate, stir well, and after a certain period of curing reaction, a molded substrate blank is formed; then, the substrate blank is placed at 510°C, 750°C, 830°C, 980°C, and 1350°C in turn for multi-stage sintering, sintering at each temperature for 25 minutes to obtain a foam ceramic substrate with a thickness of about 32mm.
[0057] While the foam ceramic substrate retains a residual temperature of about 95°C, about 2g of reinforcing slurry is evenly coated on the surface of the foam ceramic substrate, and then the carbon adsorption slurry is immediately coated on the surface of the reinforcing slurry. After cooling to room temperature, the foam ceramic board is placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105MPa for 3 minutes to obtain a foam ceramic main board with a carbon adsorption layer of about 15mm on the surface.
[0058] Take the foam ceramic main board, apply the hardening coating to the foam ceramic main board 4 times, each coating thickness is about 2.5 mm, place it under ultraviolet light for 30 minutes, and obtain the foam ceramic green plate.
[0059] The foam ceramic green sheet was transferred into a sintering furnace, heated to 1150°C at a rate of about 4.5°C / min, and sintered for 2 hours to obtain a foam ceramic material.
[0060] Example 3
[0061] The polyester fiber and the nylon fiber are mixed in equal amounts, passed through an 80-mesh sieve, added to 2.5 times the volume of the water-based polyurethane pressure-sensitive adhesive, stirred at 200 r / min for 20 min to obtain a reinforced slurry for later use;
[0062] Take 5.01 g of mesoporous silica, 4.63 g of molecular sieve and 5.61 g of polycarboxylate, mix them thoroughly, add them to α-epoxy resin and deionized water, and adjust the material viscosity to 450±2.5 mPa·s by adding α-epoxy resin or deionized water to obtain a carbon adsorption slurry for standby use;
[0063] 25 parts by mass of epoxy acrylic resin, 5.5 parts by mass of polysilsileoxane, 0.31 parts by mass of benzophenone-tertiary amine photoinitiator, 0.25 parts by mass of o-hydroxybenzophenone and 45 parts by mass of acetone were mixed and stirred at 550 r / min for 30 min to obtain a hardened coating for use.
[0064] Take 4.201g of silicon nitride, 4.3g of silicon carbide and 10.25g of aluminum oxide, add them to 75mL of deionized water, ball mill for 15 minutes, then add 1.55g of yttrium oxide, 1.20g of zirconium oxide and 2.54g of sodium dodecyl sulfate, stir well, and after a certain period of curing reaction, a molded substrate blank is formed; then, the substrate blank is placed at 510°C, 750°C, 830°C, 980°C, and 1350°C in turn for multi-stage sintering, sintering at each temperature for 25 minutes to obtain a foam ceramic substrate with a thickness of about 32mm.
[0065] While the foam ceramic substrate retains a residual temperature of about 95°C, about 5g of reinforcing slurry is evenly coated on the surface of the foam ceramic substrate, and then the carbon adsorption slurry is immediately coated on the surface of the reinforcing slurry. After cooling to room temperature, the foam ceramic board is placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105MPa for 3 minutes to obtain a foam ceramic main board with a carbon adsorption layer of about 15mm on the surface.
[0066] Take the foam ceramic main board, apply the hardening coating to the foam ceramic main board twice, each coating thickness is about 2.5 mm, place it under ultraviolet light for 30 minutes, and obtain the foam ceramic green plate.
[0067] The foam ceramic green sheet was transferred into a sintering furnace, heated to 1150°C at a rate of about 4.5°C / min, and sintered for 2 hours to obtain a foam ceramic material.
[0068] Example 4
[0069] The polyester fiber and the nylon fiber are mixed in equal amounts, passed through an 80-mesh sieve, added to 2.5 times the volume of the water-based polyurethane pressure-sensitive adhesive, stirred at 200 r / min for 20 min to obtain a reinforced slurry for later use;
[0070] Take 5.01 g of mesoporous silica, 4.63 g of molecular sieve and 5.61 g of polycarboxylate, mix them thoroughly, add them to α-epoxy resin and deionized water, and adjust the material viscosity to 450±2.5 mPa·s by adding α-epoxy resin or deionized water to obtain a carbon adsorption slurry for standby use;
[0071] 25 parts by mass of epoxy acrylic resin, 5.5 parts by mass of polysilsileoxane, 0.31 parts by mass of benzophenone-tertiary amine photoinitiator, 0.25 parts by mass of o-hydroxybenzophenone and 45 parts by mass of acetone were mixed and stirred at 550 r / min for 30 min to obtain a hardened coating for use.
[0072] Take 4.211g of silicon nitride, 4.33g of silicon carbide and 10.45g of aluminum oxide, add them to 75mL of deionized water, ball mill for 15 minutes, then add 0.61g of yttrium oxide, 0.55g of zirconium oxide and 2.52g of sodium dodecyl sulfate, stir well, and after a certain period of curing reaction, a molded substrate blank is formed; then, the substrate blank is placed at 510°C, 750°C, 830°C, 980°C, and 1350°C in turn for multi-stage sintering, sintering at each temperature for 25 minutes to obtain a foam ceramic substrate with a thickness of about 32mm.
[0073] While the foam ceramic substrate retains a residual temperature of about 95°C, about 5g of reinforcing slurry is evenly coated on the surface of the foam ceramic substrate, and then the carbon adsorption slurry is immediately coated on the surface of the reinforcing slurry. After cooling to room temperature, the foam ceramic board is placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105MPa for 3 minutes to obtain a foam ceramic main board with a carbon adsorption layer of about 15mm on the surface.
[0074] Take the foam ceramic main board, apply the hardening coating to the foam ceramic main board 4 times, each coating thickness is about 2.5 mm, place it under ultraviolet light for 30 minutes, and obtain the foam ceramic green plate.
[0075] The foam ceramic green sheet was transferred into a sintering furnace, heated to 1150°C at a rate of about 4.5°C / min, and sintered for 2 hours to obtain a foam ceramic material.
[0076] Example 5
[0077] The polyester fiber and the nylon fiber are mixed in equal amounts, passed through an 80-mesh sieve, added to 2.5 times the volume of the water-based polyurethane pressure-sensitive adhesive, stirred at 200 r / min for 20 min to obtain a reinforced slurry for later use;
[0078] Take 5.01 g of mesoporous silica, 4.63 g of molecular sieve and 5.61 g of polycarboxylate, mix them thoroughly, add them to α-epoxy resin and deionized water, and adjust the material viscosity to 450±2.5 mPa·s by adding α-epoxy resin or deionized water to obtain a carbon adsorption slurry for standby use;
[0079] 25 parts by mass of epoxy acrylic resin, 5.5 parts by mass of polysilsileoxane, 0.31 parts by mass of benzophenone-tertiary amine photoinitiator, 0.25 parts by mass of o-hydroxybenzophenone and 45 parts by mass of acetone were mixed and stirred at 550 r / min for 30 min to obtain a hardened coating for use.
[0080] Take 4.216g of silicon nitride, 4.35g of silicon carbide and 10.03g of aluminum oxide, add them to 80mL of deionized water, ball mill for 15 minutes, then add 1.6g of yttrium oxide, 1.3g of zirconium oxide and 2.66g of sodium dodecyl sulfate, stir well, and after a certain period of curing reaction, a molded substrate blank is formed; then, the substrate blank is placed at 510°C, 750°C, 830°C, 980°C, and 1350°C in turn for multi-stage sintering, sintering at each temperature for 25 minutes to obtain a foam ceramic substrate with a thickness of about 40mm.
[0081] While the foam ceramic substrate retains a residual temperature of about 95°C, about 5g of reinforcing slurry is evenly coated on the surface of the foam ceramic substrate, and then the carbon adsorption slurry is immediately coated on the surface of the reinforcing slurry. After cooling to room temperature, the foam ceramic board is placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105MPa for 3 minutes to obtain a foam ceramic main board with a carbon adsorption layer of about 10mm on the surface.
[0082] Take the foam ceramic main board, apply the hardening coating to the foam ceramic main board 4 times, each coating thickness is about 2 mm, and place it under ultraviolet light for 30 minutes to obtain a foam ceramic green plate.
[0083] The foam ceramic green sheet was transferred into a sintering furnace, heated to 1150°C at a rate of about 4.5°C / min, and sintered for 2 hours to obtain a foam ceramic material.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 1 is:
[0086] 4.35 g of silicon nitride, 4.3 g of silicon carbide and 11.0 g of aluminum oxide were added to 70 mL of deionized water, ball-milled for 15 min, and then 2.6 g of sodium dodecyl sulfate was added and stirred. After a certain period of curing reaction, a molded substrate blank was formed, and sintered at 510°C, 750°C, 830°C, 980°C and 1350°C for 2 h to obtain a foam ceramic substrate;
[0087] The carbon adsorption slurry was coated on the surface of the cooled foam ceramic substrate. After cooling to room temperature, the foam ceramic plate was placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105 MPa for 3 minutes to obtain a foam ceramic material with a carbon adsorption layer on the surface.
[0088] Comparative Example 2
[0089] The difference between this comparative example and Example 1 is:
[0090] 4.25 g of silicon nitride, 4.08 g of silicon carbide and 10.31 g of aluminum oxide were added to 75 mL of deionized water, ball-milled for 15 min, and then 2.54 g of sodium dodecyl sulfate was added and stirred. After a certain period of curing reaction, a molded substrate blank was formed, and sintered at 510°C, 750°C, 830°C, 980°C and 1350°C for 2 h to obtain a foam ceramic substrate;
[0091] After coating about 5 g of reinforcing slurry on the surface of the initially formed foam ceramic substrate which retains a residual temperature of about 95°C, the carbon adsorption slurry is immediately coated on the surface of the reinforcing slurry. After cooling to room temperature, the foam ceramic board is placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105 MPa for 3 minutes to obtain a foam ceramic material with a carbon adsorption layer on the surface.
[0092] Comparative Example 3
[0093] The difference between this comparative example and Example 1 is:
[0094] 4.28 g of silicon nitride, 4.1 g of silicon carbide and 10.55 g of aluminum oxide were added to 75 mL of deionized water, ball-milled for 15 min, and then 2.5 g of sodium dodecyl sulfate was added and stirred. After a certain period of curing reaction, a molded substrate blank was formed, and sintered at 510°C, 750°C, 830°C, 980°C and 1350°C for 2 h to obtain a foam ceramic substrate;
[0095] A carbon adsorption slurry is coated on the surface of a foam ceramic substrate at room temperature. After cooling to room temperature, the foam ceramic board is placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105 MPa for 3 minutes to obtain a foam ceramic main board with a carbon adsorption layer on the surface; the hardened coating is evenly coated on the surface of the foam ceramic main board with a thickness of about 10 mm, and is placed under an ultraviolet lamp for 30 minutes, and then sintered at 1150°C for 2 hours to obtain a foam ceramic material.
[0096] Comparative Example 4
[0097] The difference between this comparative example and Example 1 is:
[0098] 4.35 g of silicon nitride, 4.3 g of silicon carbide and 11.0 g of aluminum oxide were added to 80 mL of deionized water, and ball-milled for 15 min. Then, 1.6 g of yttrium oxide, 1.3 g of zirconium oxide and 2.66 g of sodium dodecyl sulfate were added and stirred evenly. After a certain period of curing reaction, a molded substrate blank was formed. The substrate was sintered at 510°C, 750°C, 830°C, 980°C and 1350°C for 2 h to obtain a foam ceramic substrate.
[0099] The carbon adsorption slurry was coated on the surface of the cooled foam ceramic substrate. After cooling to room temperature, the foam ceramic plate was placed in a mold, cured and air-dried, and isostatically pressed at a pressure of 105 MPa for 3 minutes to obtain a foam ceramic material with a carbon adsorption layer on the surface.
[0100] Test example
[0101] The foam ceramic materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were taken respectively, and 10 cm*10 cm square plates were randomly sampled and cut as samples. The same method and conditions were used to measure the strength, hardness and other properties of the samples according to GB / T 5072-2008 "Test Method for Normal Temperature Compressive Strength of Refractory Materials" and GB / T16534-2009 "Test Method for Room Temperature Hardness of Fine Ceramics". The results are summarized in Table 1 below:
[0102] Table 1 Performance test results of different samples
[0103]
[0104] Among them, the surface porosity is the proportion of the micropore area on the surface of the sample to the surface area; the carbon absorption rate refers to the carbon absorption rate maintained by the sample after the sample is placed in a carbon absorption furnace at 55% humidity and 300°C for 50 internal cycles.
[0105] It can be seen from Table 1 above that, compared with Comparative Examples 1 to 4, the foam ceramic material samples prepared in Examples 1 to 5 have a significantly higher surface porosity, and the carbon absorption rate finally exhibited is also correspondingly higher, which indicates that the foam ceramics proposed in the present invention can be more effectively used for carbon absorption and capture in carbon sequestration; and according to the measured compressive strength and compressive hardness results, the samples of Examples 1 to 5 also show obvious advantages, which indicates that the foam ceramics of the present invention can solve the problem of insufficient mechanical strength of existing foam ceramic materials, and are more suitable for underground carbon sequestration technology.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A foam ceramic for carbon sequestration, characterized in that: It comprises a foam ceramic substrate, a carbon adsorption layer is arranged on the surface of the foam ceramic substrate, reinforcing fibers are inserted through the foam ceramic substrate and the carbon adsorption layer, and a hard coating is also arranged on the surface of the carbon adsorption layer.
2. The foam ceramic for carbon sequestration according to claim 1, characterized in that: The thickness ratio of the foam ceramic substrate to the carbon adsorption layer is 1.2-2.8:
1.
3. The foam ceramic for carbon sequestration according to claim 2, characterized in that: The total thickness of the foam ceramic is ≤65 mm, and the thickness of the hard coating is 5-16 mm.
4. A method for preparing a foam ceramic for carbon sequestration according to any one of claims 1 to 3, characterized in that: The steps include: The surface of the foam ceramic substrate is coated with fiber sizing material, and then coated with carbon adsorption slurry, cooled to form a carbon adsorption layer, and subjected to pressing treatment to obtain a foam ceramic main board; The surface of the foam ceramic main board is coated with hardening paint for multiple times and irradiated under ultraviolet light to form a hard coating; it is then transferred into a sintering furnace, heated evenly, and sintered at a constant temperature to obtain foam ceramics.
5. The method for preparing foam ceramics for carbon sequestration according to claim 4, characterized in that: The method for preparing the foam ceramic substrate comprises the following steps: The silicon source and the aluminum source are mixed, dissolved in deionized water, ball-milled, and then a molding aid and a surfactant are added, and a substrate blank is formed through a curing reaction; The substrate blank is placed in a gradient temperature environment of 500±50°C, 750±50°C, 850±50°C, 1000±50°C, and 1350±50°C for segmented sintering to obtain the foam ceramic substrate.
6. The method for preparing foam ceramics for carbon sequestration according to claim 5, characterized in that: By mass fraction, the foam ceramic substrate comprises 12-20% silicon source, 8-15% aluminum source, 2-5.5% molding aid, 0.3-3.5% surfactant, and the balance is deionized water.
7. The method for preparing foam ceramics for carbon sequestration according to claim 4, characterized in that: The fiber sizing material comprises polyester fiber, nylon fiber and water-based polyurethane pressure-sensitive adhesive, and the fiber sizing material is coated on the foam ceramic substrate at a residual temperature of 80-110° C. while it is hot.
8. The method for preparing foam ceramics for carbon sequestration according to claim 4, characterized in that: The carbon adsorption slurry comprises porous particles, epoxy resin, polycarboxylate and water, and the viscosity of the carbon adsorption slurry is 350-620 mPa·s; Wherein, the porous particles include one or more of mesoporous silica, molecular sieves, and carbon nanomaterials.
9. The method for preparing foam ceramics for carbon sequestration according to claim 4, characterized in that: The method for preparing the hardened coating comprises the following steps: 10-30 parts of epoxy acrylic resin, 3-10 parts of polysiloxane, 0.2-0.35 parts of photoinitiator, 0.2-0.3 parts of light stabilizer and 30-50 parts of organic solvent are taken by mass, and stirred at 450-600 r / min for 30-45 minutes to obtain the hardened coating.
10. The method for preparing foam ceramics for carbon sequestration according to claim 9, characterized in that: The hardening coating is applied in 2-4 times, and the thickness of each application is ≤6mm.
